Assessing public support for commercial fishing in the ocean twilight zone considering climate trade-offs and ocean literacy - Weir, Michael J.; Lozinsky, Maya; Jin, Di (Frontiers in Marine Science, 2025)
Biomass in the mesopelagic or twilight zone (OTZ) of the ocean is estimated to be 10–100 times that of current annual capture fishery production and plays a fundamental role in regulating global climate via both biological and physical processes. Recently, OTZ fisheries have gained commercial attention to support aquaculture feed production. However, scientific uncertainty remains about the OTZ’s link to carbon cycling processes, making it difficult to craft a comprehensive policy to regulate human intervention and mitigate negative consequences. We distribute a choice experiment among U.S. residents to estimate the potential social benefit associated with expanding OTZ fisheries and whether ocean-literate individuals experience a different degree of benefits. We find that ocean-literate individuals are more likely to support positive levels of OTZ sourced seafood production relative to non-ocean-literate individuals. Average individual annual benefits range from $1.84 to $124.74 conditional on ocean literacy and harvest policy attributes. Ocean-literate individuals are estimated to experience benefits two to three times higher than those who are not ocean literate across all harvest policy scenarios, suggesting significant heterogeneity in the distribution of OTZ-derived benefits conditional on ocean literacy. While our results suggest significant social benefits to be gained from expanding OTZ fishery production, back-of-the-envelope calculations suggest that rapid development of OTZ fishing would likely induce social costs more than 10× that of any benefits experienced. As such, we recommend careful exercise of the precautionary principle in consideration of mesopelagic governance approaches and industry expansion.